2022
DOI: 10.14744/agri.2021.80270
|View full text |Cite
|
Sign up to set email alerts
|

Validity And Reliability of The Full Cup Test In Patients With Chronic Low Back Pain

Abstract: This study aims to determine the validity and reliability of the full cup test (FCT), evaluating the pain severity in patients with chronic low back pain. Methods: A total of 100 patients (70 women and 30 men) aged over 18 years with mechanical low back pain were enrolled in the study. Demographic and clinical characteristics were recorded. Pain severity was evaluated using the visual analog scale (VAS) and FCT, the functional state was assessed by the Oswestry Disability Index (ODI), and the quality of life w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Our study indicated a significant level of agreement amongst the raters, i.e., value of 0.596 (p < 0.0001), in assessing pain intensity using the selected pain scale similar to another study done by Hatice Agir in Turkey in 2022. 22 Our findings suggest that the pain scale utilized in our study aptly captured and expressed varying degrees of pain intensity, supporting its utility in clinical practice for accurate pain assessment, Table -IV. The subjective nature of pain and clinician discretion makes pain management susceptible to significant disparities across racial, ethnic, and language-based patient factors.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Our study indicated a significant level of agreement amongst the raters, i.e., value of 0.596 (p < 0.0001), in assessing pain intensity using the selected pain scale similar to another study done by Hatice Agir in Turkey in 2022. 22 Our findings suggest that the pain scale utilized in our study aptly captured and expressed varying degrees of pain intensity, supporting its utility in clinical practice for accurate pain assessment, Table -IV. The subjective nature of pain and clinician discretion makes pain management susceptible to significant disparities across racial, ethnic, and language-based patient factors.…”
Section: Discussionsupporting
confidence: 68%
“…These findings suggest that the FCT may be a more accessible and easier-to-understand pain assessment tool for individuals with limited educational backgrounds. 10 , 12 , 20 , 22 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations